The Structure of Multidimensional Perfectionism: Support for a Bifactor Model With a Dominant General Factor. Issue 3 (4th May 2017) - Smith, Martin M.; Saklofske, Donald H.
ABSTRACT: Evidence suggests perfectionism is a multidimensional construct composed of 2 higher order factors: perfectionistic strivings and perfectionistic concerns. However, the substantial overlap between perfectionistic strivings and perfectionistic concerns is problematic, as are the unanswered questions regarding the structure of perfectionism following removal of common variance. This research addressed this through bifactor modeling. Three student samples ( N = 742) completed Hewitt and Flett's (1991 ) Multidimensional Perfectionism Scale, Frost, Marten, Lahart, and Rosenblate's (1990 ) Multidimensional Perfectionism Scale, and Slaney, Rice, Mobley, Trippi, and Ashby's (2001 ) Almost Perfect Scale–Revised. Greater support was consistently found for the bifactor model, relative to the 2-factor model. Results suggest the bifactor model best represents the structure of perfectionism and provide preliminary support for the use of a general factor score. Researchers are cautioned that removal of general variance may render the reliability of specific factors (i.e., perfectionistic strivings and perfectionistic concerns) suspect.